2016
DOI: 10.1371/journal.pone.0168743
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Misclassification between Neonatal Deaths and Stillbirths: Empirical Evidence from Malawi

Abstract: Improving the counting of stillbirths and neonatal deaths is important to tracking Sustainable Development Goal 3.2 and improving vital statistics in low- and middle-income countries (LMICs). However, the validity of self-reported stillbirths and neonatal deaths in surveys is often threatened by misclassification errors between the two birth outcomes. We assessed the extent and correlates of stillbirths being misclassified as neonatal deaths by comparing two recent and linked population surveys conducted in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 24 publications
5
66
0
Order By: Relevance
“…[13] This figure is more closely aligned with the global estimate that 45% of under-5 deaths occur during the newborn period, [21] but may be artificially high owing to misclassification of stillbirths as neonatal death, which has been shown to occur during such surveys in other countries. [14,15] …”
Section: National Estimates Of Under-5 Deaths and Mortality Ratesmentioning
confidence: 99%
“…[13] This figure is more closely aligned with the global estimate that 45% of under-5 deaths occur during the newborn period, [21] but may be artificially high owing to misclassification of stillbirths as neonatal death, which has been shown to occur during such surveys in other countries. [14,15] …”
Section: National Estimates Of Under-5 Deaths and Mortality Ratesmentioning
confidence: 99%
“…Secondly, SADHS data come from questionnaires administered to mothers in the community; therefore, it is possible that the recall of these mothers includes stillbirths. This explanation is informed by a recent Malawian study [37] that found that in contrast, 20% of neonatal deaths were wrongfully classified as stillbirths after a full birth history by the mother. StatsSA and the MRC will review the SADHS data to confirm whether the SA NMR is double the current DHIS estimates.…”
Section: Researchmentioning
confidence: 99%
“…As an example, a study comparing two population surveys conducted in Malawi found that one-fifth of neonatal deaths identified in the full birth history (FBH) survey were classified as stillbirths in the verbal/social autopsy (VASA) survey. 8 Moreover, verification of data quality of childbirth registers in rural hospitals in Kenya demonstrated that the list of labor and delivery variables was incorrectly and inappropriately coded, 9 and that data quality of the childbirth registers was unsatisfactory. Improvement in accounting of neonatal mortality and live births will require improved hospital-based recording and its linkage with vital registration systems.…”
Section: Introductionmentioning
confidence: 99%